Adapting a Measure of Socially Responsible Consumption in France to the Vietnamese Context A Study in Ho Chi Minh City - Xuan, Le Thi Thanh; Tai, Lai Van (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2016)
Abstract The major aim of this study is to employ the measure of socially responsible consumption (SRC) developed by Francois-Lecompte and Roberts (2006) to empirically explore the level of Vietnamese consumers’ awareness of SRC. Consumers inHo Chi Minh Citywere approached in order to distribute questionnaires in stores, supermarkets, shopping malls, traditional markets, etc. Data gathered from the survey was processed by SPSS 21 software. In analysis of the data, exploratory factor analysis technique is applied to explore the correlations of variables and factors formation. Principle component analysis with the Promax rotation method is used in this process. Reliability of measurement scales presented in each factor is tested by Cronbach’s Alpha. And, ANOVA analysis is also applied to test the differences of SRC behaviors between customers of demographic profiles. Research findings have shown some salient points. Firstly, the order of SRC factors in Vietnamese consumers’ perspectives is different from that inFrance. Secondly, 17 of 20 variables to measure SRC factors can be used to conduct a SRC study inVietnam. However, it is necessary to conduct a qualitative study to develop a measure more appropriate to Vietnamese consumers. Received 24 March 2016, revised 9 June 2016, accepted 28 June 2016 Keywords: Socially responsible consumption, ethical consumption, Vietnam.